2018
DOI: 10.1007/s40534-018-0173-y
|View full text |Cite
|
Sign up to set email alerts
|

Modified criterion for prediction of tunnel deformation in non-squeezing ground conditions

Abstract: The strength factor-based criterion for tunnel deformation prediction proposed by Hoek in 2000 is reckoned to be the most practical criterion among the tunnel deformation criteria since 1980s. In view of the fact that Hoek's criterion was obtained based on case studies under squeezing ground conditions, it has a limited range of applications, applicable mainly in squeezing tunnels. In this work, this criterion was modified by taking into consideration the conditions of eight unstable stations in three non-sque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…This often leads to roof collapse, floor heave, sidewall heave, and other accidents, which significantly impact coal mine safety production [5,6]. By collecting the amount of surrounding rock deformation and analyzing its changing trend, the safety condition of the roadway can be evaluated [7,8]. For example, in the article [9], through long-term geotechnical engineering monitoring, it was found that the deformation of roadway roof strata is affected by the support scheme, roof stratification, and rock strength, and the relationship between the support scheme and surrounding rock movement was summarized according to the monitoring results.…”
Section: Introductionmentioning
confidence: 99%
“…This often leads to roof collapse, floor heave, sidewall heave, and other accidents, which significantly impact coal mine safety production [5,6]. By collecting the amount of surrounding rock deformation and analyzing its changing trend, the safety condition of the roadway can be evaluated [7,8]. For example, in the article [9], through long-term geotechnical engineering monitoring, it was found that the deformation of roadway roof strata is affected by the support scheme, roof stratification, and rock strength, and the relationship between the support scheme and surrounding rock movement was summarized according to the monitoring results.…”
Section: Introductionmentioning
confidence: 99%
“…The groundmass underwent multiple periods of deformation owing to the collision of the Indian and Eurasian plates, weakening the rocks of the sub-and lower Himalayas [4]. Construction on or through this distorted groundmass is thus difficult [5].…”
Section: Introductionmentioning
confidence: 99%